GENDER OPPRESSION IN THE WORKPLACE DEPICTED IN FILM THE ASSISTANT (2019) - Safitri, Dian Ari; Februansyah, Rizki; Aeni, Eni Nur (Universitas Brawijaya, 2023)
Gender issues are endless issues to be studied. The increasing number of women entering the workforce makes gender issues becoming increasingly interesting to discuss. One of the films that raised the issue of gender in the workplace is The Assistant (2019). This current study aims to analyse the issue of gender oppression experienced by the main female character in the film who works in a male-dominated company, especially those related to cultural imperialism. It uses a qualitative method using dialogue as the main data. These data will be analysed using the theory of the Five Faces of Oppression by Iris M. Young. The results of this study indicate that Jane experiences cultural imperialism which is influenced by the social norms prevailing in patriarchal culture. The cultural imperialism also triggers other forms of oppression which include the marginalization of women, exploitation of labour, and the powerlessness towards male co-workers and superiors. These oppressions occurred because of Jane's status as a woman and her position as an assistant. Jane experiences oppression because social norms and practices governing gender roles in society are also still applied in the workplace. Eventually, this research reveals that tasks that are usually done by women outside of their responsibilities can be categorized as oppression in the form of cultural imperialism which can reinforce oppression in other forms. Therefore, gender awareness is needed to be able to minimize acts of oppression for women in the workplace.